Organizational complexity and balance sheet management in global banks - Nicola Cetorelli; Linda S. Goldberg (Federal Reserve Bank of New York, 2016)
Banks have progressively evolved from being standalone institutions to being subsidiaries of increasingly complex financial conglomerates. We conjecture and provide evidence that the organizational complexity of the family of a bank is a fundamental driver of the business model of the bank itself, as reflected in the management of the bank's own balance sheet. Using micro-data on global banks with branch operations in the United States, we show that branches of conglomerates in more complex families have a markedly lower lending sensitivity to funding shocks. The balance sheet management strategies of banks are very much determined by the structure of the organizations the banks belong to. The complexity of the conglomerate can change the scale of the lending channel for a large global bank by more than 30 percent.
Keywords: E44; F36; G32; 330; global bank; liquidity; transmission; internal capital market; organization; complexity; Internationale Bank; Ausländisch; Organisationsstruktur; Ausländische Tochtergesellschaft; Komplexitätsmanagement; Bilanzstrukturmanagement; Kreditgeschäft; Schätzung; USA